SALINITY TOLERANCE OF SEVERAL RICE GENOTYPES AT SEEDLING STAGE - Heni Safitri; Bambang Sapta Purwoko; Iswari Saraswati Dewi; Sintho Wahyuning Ardie (Indonesian Journal of Agricultural Science, 2017)
Salinity is one of the most serious problems in rice cultivation. Salinity drastically reduced plant growth and yield, especially at seedling stage. Several rice genotypes have been produced, but their tolerance to salinity has not yet been evaluated. The study aimed to evaluate salinity tolerance of rice genotypes at seedling stage. The glasshouse experiment was conducted at Cimanggu Experimental Station, Bogor, from April to May 2013. Thirteen rice genotypes and two check varieties, namely Pokkali (salt tolerant) and IR29 (salt sensitive) were tested at seedling stage. The experiment was arranged in a randomized complete block design with three replications and two factors, namely the levels of NaCl (0 and 120 mM) and 13 genotypes of rice. Rice seedlings were grown in the nutrient culture (hydroponic) supplemented with NaCl at different levels. The growth and salinity injury levels of the genotypes were recorded periodically. The results showed that salinity level of 120 mM NaCl reduced seedling growth of all rice genotypes, but the tolerant ones were survived after 14 days or until the sensitive check variety died. Based on the visual injury symptoms on the leaves, five genotypes, i.e. Dendang, Inpara 5, Inpari 29, IR77674-3B-8-2-2-14-4-AJY2, and IR81493-BBB-6-B- 2-1-2 were tolerant to 120 mM salinity level, while Inpara 4 was comparable to salt sensitive IR29. Hence, Inpara 4 could be used as a salinity sensitive genotype for future research of testing tolerant variety. Further evaluation is needed to confirm their salinity tolerance under field conditions.